2017
DOI: 10.1080/1828051x.2017.1340097
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of dietary multi-species probiotic on growth performance, nutrient digestibility, meat quality traits, faecal microbiota and diarrhoea score in growing–finishing pigs

Abstract: This study evaluated the effects of multi-species probiotic (MSP) in growing-finishing pigs. One hundred and fifty pigs [(Yorkshire  Landrace)  Duroc] with an average weight of 24.5 ± 0.88 kg were fed in two phases in a 16-week trial. Pigs were allotted to one of three diets with basal diet supplemented with 0, 0.1 or 0.2 g/kg MSP. Dietary inclusion of MSP increased (p < .05) body weight, average daily gain and gain:feed without effects of average daily feed intake at overall experiment and apparent total tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 27 publications
5
33
1
Order By: Relevance
“…The use of the Bokashi preparation did not have a significant statistical effect on meat marbling. This is consistent with the results from Balasubramanian et al [ 35 ], but different from Meng et al [ 5 ]. Marbling is defined as the amount and spatial distribution of visible, white fat spots present in meat.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The use of the Bokashi preparation did not have a significant statistical effect on meat marbling. This is consistent with the results from Balasubramanian et al [ 35 ], but different from Meng et al [ 5 ]. Marbling is defined as the amount and spatial distribution of visible, white fat spots present in meat.…”
Section: Resultssupporting
confidence: 89%
“…The application of the Bokashi preparation did not have a significant statistical effect on the change of meat color (L*a*b*) in the study groups. A study by Balasubramanian et al [ 35 ] also showed no effect of the addition of the probiotic on meat color (L*: 58.42; a*: 17.47; b*: 6.10 at a supplementation of 0.1 MSP g/kg). Other authors, on the other hand, noted a much higher proportion of yellow among the group of pigs fed the probiotic (8.98 vs. 9.48; p < 0.05) [ 18 ].…”
Section: Resultsmentioning
confidence: 97%
“…Chen et al (2005) indicated that a diet enriched with a probiotic preparation (Lactobacillus acidophilus, 1.0 × 10 7 CFU (colony-forming unit)/g; Saccharomyces cerevisae, 4.3 × 10 6 CFU/g; and Bacillus subtilis 2.0 × 3 × 10 6 CFU/g) had a beneficial effect on the BW and growth rate. Similarly, the studies conducted by Balasubramanian, Sang, and Kim (2018) showed that the introduction of a probiotic (Bacillus coagulans, 1 × 10 9 CFU/g; B. licheniformis, 5 × 10 8 CFU/g; B. subtilis, 1 × 10 9 CFU/g; and Clostridium butyricum 1 × 10 8 CFU/g) into the animal diet significantly (p < .05) increased BW and ADG. Mahan, Cromwell, Ewan, Hamilton, and Yen (1998) and Quiniou, Dagorn, and Gaudre (2002) also reported that animals from a group fed with a probiotic additive had significantly higher (p < .01) growth rates, with lower FCR.…”
Section: The Fattening Performancementioning
confidence: 69%
“…In contrast to our study, higher digestibility of all nutrients was observed in pigs fed different probiotics like Bacillus and L . acidophilus [ 62 ].…”
Section: Discussionmentioning
confidence: 99%